Peningkatan Sikap Gotong Royong pada Pembelajaran PPKn melalui Cooperative Learning Tipe Jigsaw Kelas IV Sekolah Dasar - Moh. Hadirih; Afib Rulyansah; M. Mustofa Kamal (STKIP AL HIKMAH SURABAYA, 2023)
The aim of this research is to determine the increase in the attitude of mutual cooperation as a character of the Pancasila Student Profile through the implementation of PPKn learning with a jigsaw type cooperative learning model for grade IV Bilal students at Khadijah Pandegiling Elementary School, Surabaya. This type of research is classroom action research (PTK). The data collection method uses mutual cooperation attitude observation sheets and learning implementation observation sheets. The results of the research showed that there was an increase in the percentage of mutual cooperation attitudes from before the action, 8% in the good category, increased in cycle I to 29% in the good category, and increased again by 50% in the good category and 38% in the very good category in cycle II. It can be concluded that the application of the jigsaw type cooperative learning model is able to improve the mutual cooperation attitude of class IV Bilal students at Khadijah Pandegiling Elementary School, Surabaya.